Knowledge management practices and sustainability reporting: the mediating role of intellectual capital - Kyeyune Nakyeyune, Gorrettie; Bananuka, Juma; Tumwebaze, Zainabu; Kezaabu, Saphurah (Journal of Money and Business, 2022)
This study’s aim is twofold: First, to establish the relationship between intellectual capital, knowledge management practices and sustainability reporting practices; second, to examine the mediating role of intellectual capital in the relationship between knowledge management practices and sustainability reporting practices. Design/methodology/approach – This study is cross-sectional and uses a questionnaire survey of accountants in the financial services firms in Uganda. The data were analyzed using Statistical Package for Social Sciences and MediGraph program (Excel version). Findings – Results indicate that intellectual capital and knowledge management practices are significantly related to the sustainability reporting practices among financial services firms in Uganda. Also, intellectual capital mediates the relationship between knowledge management practices and sustainability reporting practices. Originality/value – Using perceptions, this study demonstrates how internal resources and capabilities can promote sustainability reporting in financial services firms in developing countries. Specifically, this study provides first time evidence on the mediating role of intellectual capital in the relationship between knowledge management practices and sustainability reporting practices.
Keywords: Sustainability reporting practices; Knowledge management practices; Intellectual capital; Financial services firms; Uganda